A negative electrode sheet, a method for manufacturing the same, and an application thereof

CN123033951APending Publication Date: 2026-11-03JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611285857.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-24
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

In lithium-ion battery anode sheets, excessive addition of binder can lead to a decrease in the proportion of active material, blockage of electron conduction pathways, and poor electrolyte permeability, affecting the battery's specific capacity, energy density, rate performance, and consistency.

Method used

By attaching amino or hydroxyl groups to the surface of the active material, a chemical reaction occurs with the carboxyl groups on the surface of the conductive agent, forming chemical bonds and constructing a conductive agent network structure. This achieves a stable bridging between the active material and the conductive agent, reducing the binder content.

Benefits of technology

By reducing the binder content, the electrode structure remains stable, the electron transport path is improved, the electron transport rate and structural stability are increased, and the high-rate charge-discharge and cycle stability are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123033951A_ABST
    Figure CN123033951A_ABST
Patent Text Reader

Abstract

The application provides a negative electrode sheet and a preparation method and application thereof. The negative electrode sheet comprises a current collector, an active coating layer, the active coating layer comprises an active material, a conductive agent and a binder, the mass content of the binder in the active coating layer is less than or equal to 5%, the active material contains an amino group or a hydroxyl group, and the conductive agent contains a carboxyl group. The negative electrode sheet provided by the application can form a chemical bond between the active material and the conductive agent by connecting the amino group or the hydroxyl group on the surface of the active material with the carboxyl group on the surface of the conductive agent, so that the active material can be firmly bridged on the surface of the network structure of the conductive agent, and the shedding of the active layer is avoided. Therefore, the negative electrode sheet provided by the application can still have a stable electrode sheet structure after the content of the binder is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of batteries, and in particular relates to a negative electrode sheet, its preparation method and application. Background Technology

[0002] In the preparation of negative electrode sheets for lithium-ion batteries, binders are an indispensable key auxiliary component. However, in actual production, excessive binder addition can lead to a series of technical defects, affecting the overall performance of lithium batteries and limiting their application in various electronic devices, new energy vehicles, and other fields. Specifically, binders are inert components that do not participate in lithium insertion-extraction reactions. Excessive addition directly reduces the space available for active materials (such as graphite and silicon-based materials) in the negative electrode sheet, resulting in a decrease in the content of active materials and a significant drop in the battery's specific capacity and energy density. Furthermore, most binders are electronically insulating polymers with poor ion conductivity. When excessive binder is used, a thick insulating layer forms between the active material particles. This insulating layer not only blocks the electron conduction pathway between the active material particles but also lengthens the lithium-ion diffusion path, leading to a significant increase in the electrode impedance of the negative electrode sheet and the entire lithium battery, thus deteriorating the battery's rate performance. Furthermore, excessive binder can easily form a dense film on the surface of the negative electrode. This dense film severely hinders the penetration of the electrolyte into the interior of the negative electrode, resulting in poor wetting effect of the electrolyte on the negative electrode. This not only causes uneven wetting of the negative electrode, affecting the consistency of the lithium battery, but also makes the negative electrode prone to lithium plating and increased side reactions in local areas, further deteriorating the performance of the lithium battery. Therefore, how to reasonably control the amount of binder in the negative electrode and avoid the above-mentioned defects caused by excessive binder has become an urgent technical problem to be solved in the field of lithium battery negative electrode preparation. Summary of the Invention

[0003] In view of this, this application aims to provide a negative electrode sheet, its preparation method and application, so as to reduce the binder content in the negative electrode sheet.

[0004] To solve the above-mentioned technical problems, this application is implemented as follows: According to a first aspect of this application, a negative electrode is provided, the negative electrode comprising a current collector; an active coating comprising a modified active material, a functionalized conductive agent, and a binder, wherein the binder comprises ≤5% by mass in the active coating; the modified active material contains amino or hydroxyl groups, and the functionalized conductive agent contains carboxyl groups.

[0005] The negative electrode sheet provided in this application establishes a chemical bond between the active material and the conductive agent by attaching amino or hydroxyl groups to the surface of the active material and reacting chemically with the carboxyl groups on the surface of the conductive agent. This firmly bridges the active material to the network structure of the conductive agent, preventing the active layer from detaching. Therefore, the negative electrode sheet provided in this application maintains a stable electrode structure even with a reduced binder content. On the other hand, from a microscopic perspective, electron transfer between the active material and the conductive agent without chemical bonding relies solely on physical contact. The contact gap, interfacial impedance, and dispersion uniformity between the active material and the conductive agent affect the electron transfer path, causing problems such as breakage and detours, resulting in significant resistance to electron transport at the interface between the active material and the conductive agent. Furthermore, the low adhesion between the materials means that relative displacement can disrupt the contact stability between them. Through the aforementioned chemical bonding, the active material and the conductive agent network structure are anchored point-to-point, eliminating the microscopic gaps between their interfaces. This allows electrons to travel directly from the surface of the active material to the conductive agent without crossing physical contact gaps, significantly reducing interfacial contact impedance. Simultaneously, this chemical bonding uniformly anchors the dispersed active material onto the conductive agent's network framework, preventing aggregation or detachment from the network. This ensures that each active material forms an effective electronic connection with the conductive agent, constructing a continuous and dense electron transport network of "conductive agent network backbone - chemical bonds - active material." This electron channel not only improves the continuity and rate of electron transport but also disperses electron transport pressure, preventing polarization caused by localized electron accumulation. Furthermore, it enhances the structural stability of the electron channel. Even during battery charging and discharging, when the active material expands and contracts, the chemical bonding maintains the integrity of the electron channel, effectively reducing electron transport interruptions caused by interface separation. This provides microscopic-level electron transport assurance for the battery's high-rate charge / discharge performance and cycle stability.

[0006] Preferably, the negative electrode comprises: a first coating disposed on the surface of the current collector; a second coating disposed on the surface of the first coating away from the current collector; the first coating comprising a first active material, a first conductive agent, and a first binder, and the second coating comprising a second active material, a second conductive agent, and a second binder; the first active material, and / or the second active material comprising a modified active material; the first conductive agent, and / or the second conductive agent comprising a functionalized conductive agent.

[0007] Preferably, (1) the first active material and / or the second active material comprises at least one of graphite, hard carbon, and lithium titanate; (2) in the first active coating, the mass percentage of the first binder is 0.5% to 4%, and / or, in the second active coating, the mass percentage of the second binder is 0.5% to 4%; (3) both the first active material and the second active material comprise modified active materials; (4) both the first conductive agent and the second conductive agent comprise functionalized conductive agents; (5) the first conductive agent and / or the second conductive agent comprise carbon nanotubes, the carbon nanotubes have a length of 5 μm to 30 μm, and the carbon nanotubes have a pipe diameter of 0.4 nm to 2 nm; (6) the first coating has a thickness of 50 μm to 70 μm, and the second coating has a thickness of 5 μm to 20 μm.

[0008] Preferably, the second coating further comprises an oxide electrolyte, and the oxide electrolyte comprises at least one of a lithium lanthanum zirconium oxygen-based electrolyte material, a sodium superionic conductor-based electrolyte material, and a lithium aluminum titanium phosphate-based electrolyte material.

[0009] Preferably, a third coating is further provided, and the third coating is arranged on the surface of the second coating away from the current collector; the third coating comprises a third active material, and the third active material comprises a silicon-based material.

[0010] Preferably, at least one of the following conditions is satisfied: (1) the third active material comprises graphite and a silicon-oxygen material, and the chemical formula of the silicon-oxygen material is SiO x , where 0<x≤2; (2) the third coating further comprises a third conductive agent, and the oil absorption value of the third conductive agent is 60mL / 100g to 500mL / 100g; (3) the thickness of the third coating is 50μm to 70μm.

[0011] Preferably, in the third active material, calculated by mass ratio, graphite: silicon-oxygen material = 1~99:1.

[0012] According to the second aspect of the present application, the present application provides a method for preparing the negative electrode sheet as described above, comprising the following steps: S1. subjecting the active material to plasma treatment to obtain a modified active material; S2. mixing the modified active material, the functionalized conductive agent, the binder, and a solvent to obtain a negative electrode slurry; S3. coating the negative electrode slurry on the surface of a current collector, followed by drying and rolling to obtain the negative electrode sheet.

[0013] Preferably, the step of plasma treatment comprises: subjecting the active material to plasma treatment in a treatment atmosphere; the treatment atmosphere comprises a modifying gas and an inert gas, and the modifying gas comprises at least one of ammonia, hydrazine, O2, air, water vapor, and alcohol vapor.

[0014] According to the third aspect of the present application, the present application provides a battery, and the battery comprises the negative electrode sheet as described above, or the negative electrode sheet prepared by the preparation method described above.

[0015] The technical solution of this application has at least the following beneficial effects: The negative electrode sheet provided by this application forms a chemical bond between the active material and the conductive agent by connecting amino or hydroxyl groups to the surface of the active material and reacting with the carboxyl groups on the surface of the conductive agent. Utilizing this chemical bond, the negative electrode sheet provided by this application can maintain a stable electrode structure even after reducing the binder content; furthermore, it can improve the contact gap, interfacial impedance, and dispersion uniformity between the active material and the conductive agent, thereby increasing the electron transport rate, enhancing the structural stability of the electron channel, and providing microscopic protection for high-rate charge / discharge and cycle stability.

[0016] Other features and advantages of this application will be described in detail in the following detailed description section. Attached Figure Description

[0017] Figure 1 This is a schematic diagram of the negative electrode sheet provided in Example 1. Detailed Implementation

[0018] This application discloses a negative electrode sheet, its preparation method, and its application. Those skilled in the art can refer to the content of this document and appropriately modify the process parameters to achieve the desired result. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art and are considered to be included in this application. The methods and applications of this application have been described through preferred embodiments. Those skilled in the art can clearly modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit, and scope of this application to realize and apply the technology of this application.

[0019] In the description of this application, the list of items connected by the term "at least one of" or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, then the phrase "at least one of A and B" means only A; only B; or A and B. In another instance, if items A, B, and C are listed, then the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single element or multiple elements. Item B may contain a single element or multiple elements. Item C may contain a single element or multiple elements.

[0020] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and should be understood to include values ​​close to these ranges or values. For numerical ranges, endpoint values ​​of various ranges, endpoint values ​​of multiple ranges, or individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein. Unless otherwise stated, all embodiments and optional embodiments of this application can be combined with each other to form new technical solutions.

[0021] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.

[0022] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.

[0023] In order to reduce the binder content in the negative electrode, this application provides a negative electrode, its preparation method and application.

[0024] The first aspect of this application provides a negative electrode sheet, the negative electrode sheet comprising a current collector; an active coating comprising a modified active material, a functionalized conductive agent, and a binder, wherein the mass percentage of the binder in the active coating is ≤5%; the modified active material contains amino or hydroxyl groups, and the functionalized conductive agent contains carboxyl groups.

[0025] The negative electrode sheet provided in this application establishes a chemical bond between the active material and the conductive agent by attaching amino or hydroxyl groups to the surface of the active material and reacting chemically with the carboxyl groups on the surface of the conductive agent. This firmly bridges the active material to the network structure of the conductive agent, preventing the active layer from detaching. Therefore, the negative electrode sheet provided in this application maintains a stable electrode structure even with a reduced binder content. On the other hand, from a microscopic perspective, electron transfer between the active material and the conductive agent without chemical bonding relies solely on physical contact. The contact gap, interfacial impedance, and dispersion uniformity between the active material and the conductive agent affect the electron transfer path, causing problems such as breakage and detours, resulting in significant resistance to electron transport at the interface between the active material and the conductive agent. Furthermore, the low adhesion between the materials means that relative displacement can disrupt the contact stability between them. Through the aforementioned chemical bonding, the active material and the conductive agent network structure are anchored point-to-point, eliminating the gaps between their interfaces. This allows electrons to travel directly from the surface of the active material to the conductive agent without crossing physical contact gaps, significantly reducing interfacial contact impedance. Simultaneously, this chemical bonding uniformly anchors the dispersed active material onto the conductive agent's network framework, preventing aggregation or detachment from the network. This ensures that each active material forms an effective electronic connection with the conductive agent, constructing a continuous and dense electron transport network of "conductive agent network backbone - chemical bonds - active material." This electron channel not only improves the continuity and rate of electron transport but also disperses electron transport pressure, preventing polarization caused by localized electron accumulation. Furthermore, it enhances the structural stability of the electron channel. Even during battery charging and discharging, when the active material expands and contracts, the chemical bonding maintains the integrity of the electron channel, effectively reducing electron transport interruptions caused by interface separation. This provides microscopic-level electron transport assurance for the battery's high-rate charge / discharge performance and cycle stability.

[0026] In one embodiment of this application, the negative electrode sheet includes: a first coating disposed on the surface of the current collector; a second coating disposed on the surface of the first coating away from the current collector; the first coating includes a first active material, a first conductive agent, and a first binder, and the second coating includes a second active material, a second conductive agent, and a second binder; the first active material, and / or the second active material includes a modified active material; the first conductive agent, and / or the second conductive agent includes a functionalized conductive agent.

[0027] Currently, the coating processes for lithium-ion battery anode sheets are mainly single-layer and double-layer. Existing single-layer coating processes are simple and low-cost, suitable for low-area-density anode sheets. However, when preparing high-area-density sheets, increasing the coating thickness in a single step easily leads to problems such as poor uniformity, edge overflow, and surface roughness. Furthermore, internal stress during drying can cause the sheet to warp and crack. Single-layer anode sheets have uniform composition, making it impossible to simultaneously meet the requirements of current collector bonding, active material expansion buffering, and surface ion conduction. High-expansion active materials (such as silicon-based materials) are prone to pulverization and detachment due to stress concentration, shortening cycle life. In addition, in single-layer coating, the thick coating layer also prolongs the lithium-ion diffusion path; thickness deviations can interfere with electron conduction, increase polarization, worsen batch consistency, and reduce rate performance. Existing double-layer coatings divide the total thickness into two layers, improving thickness uniformity, reducing warping and cracking, and enabling simple component partitioning, allowing the bottom layer to focus on bonding and the surface layer on conduction, thus improving both adhesion and conductivity. However, the two-layer interface is not firmly bonded and is prone to delamination. Thickness control precision remains limited, the composition gradient design is simple and the transition is abrupt, easily leading to stress concentration. It cannot adequately buffer the volume expansion of silicon-based materials, making it difficult to simultaneously achieve high energy density, high rate performance, and long cycle life. To address these issues, this application provides a negative electrode comprising a first coating and a second coating, specifically addressing the need for developing high areal density electrodes. Both the first and second active materials contain amino or hydroxyl groups, while both the first and second conductive agents contain carboxyl groups. Within the same layer or between different layers, the active material undergoes amylation treatment, and the conductive agent contains carboxyl groups, which improves the connection between the active material and the conductive agent within the same layer or between different layers. This enhances the interfacial bonding force between the two layers, reducing the amount of binder while maintaining the adhesion of the active layer.

[0028] In one embodiment of this application, (1) the first active material and / or the second active material includes at least one of graphite, hard carbon, and lithium titanate; (2) in the first active coating, the mass percentage of the first binder is 0.5% to 4%, and / or in the second active coating, the mass percentage of the second binder is 0.5% to 4%; (3) both the first active material and the second active material include modified active materials; (4) both the first conductive agent and the second conductive agent include functionalized conductive agents; (5) the first conductive agent and / or the second conductive agent include carbon nanotubes, the length of which is 5 μm to 30 μm and the diameter of which is 0.4 nm to 2 nm; (6) the thickness of the first coating is 50 μm to 70 μm and the thickness of the second coating is 5 μm to 20 μm. For example, the mass percentage of the first binder can be 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, or 5%, etc.; the mass percentage of the second binder can be 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, or 5%, etc.; the length of the carbon nanotubes can be 5μm, 10μm, 15μm, 20μm, 25μm, 30μm, etc.; the diameter of the carbon nanotubes can be... The thicknesses are 0.4nm, 0.8nm, 1.2nm, 1.4nm, 1.6nm, 1.8nm, 2.0nm, etc.; the thickness of the first coating can be 50μm, 55μm, 60μm, 65μm, 70μm, etc.; the thickness of the second coating can be 5μm, 7μm, 9μm, 11μm, 13μm, 15μm, 17μm, 19μm, 20μm, etc.; however, it is not limited to the listed values, and other unlisted values ​​within this range are also applicable. The carbon nanotubes contain carboxyl groups.

[0029] In one embodiment of this application, the second coating further includes an oxide electrolyte, which includes at least one of lithium lanthanum zirconium oxide electrolyte materials, sodium superionic conductor electrolyte materials, and lithium titanium aluminum phosphate electrolyte materials. This application does not impose any particular limitation on the source of the aforementioned oxide electrolyte; commercially available products well known to those skilled in the art can be used. Furthermore, by introducing an oxide electrolyte into the second coating, the ionic conductivity of the negative electrode can be further enhanced.

[0030] In one embodiment of this application, the first coating comprises a first active material, a first dispersant, a first binder, and a first conductive agent, wherein the mass ratio of the first active material, the first dispersant, the first binder, and the first conductive agent is 90%~97%: 0.5%~5%: 0.5%~2%: 0.5%~5%.

[0031] In one embodiment of this application, the second coating comprises a second active material, a second dispersant, a second binder, a second conductive agent, and an oxide electrolyte, wherein the mass ratio of the second active material, the second dispersant, the second binder, the second conductive agent, and the oxide electrolyte is 80%~95%: 0.5%~5%: 0.5%~2%: 0.5%~5%: 2%~15%.

[0032] In one embodiment of this application, the negative electrode further includes a third coating, which is disposed on the surface of the second coating away from the current collector; the third coating includes a third active material, which includes a silicon-based material. In the prior art, whether the negative electrode structure is single-layer coated or double-layer coated, it is still necessary to improve the volume expansion of the silicon material. In this application, the negative electrode is provided with a first coating, a second coating, and a third coating, and a silicon-based material is introduced into the third coating. The first coating (bottom layer) and the second coating (intermediate layer) near the current collector are bonded by using active materials containing amino or hydroxyl groups, which significantly improves the adhesion between the bottom and intermediate layers of the negative electrode, and avoids the separation of the silicon-based material in the third coating from the current collector due to expansion during lithium intercalation.

[0033] In one embodiment of this application, the negative electrode further includes a third coating, and the second coating further includes an oxide electrolyte. The second coating has a "bridging" function; by adding the oxide electrolyte to the second coating, the oxide electrolyte can act as a lithium-ion transport bridge, constructing an ion channel from the surface layer to the current collector layer, thereby increasing the ionic conductivity of the negative electrode.

[0034] In one embodiment of this application, at least one of the following conditions is met: (1) the third active material includes graphite and silicon-oxygen materials, wherein the chemical formula of the silicon-oxygen materials is SiO2. x, wherein 0<x≤2; (2) The third coating further comprises a third conductive agent, and the oil absorption value of the third conductive agent is 60mL / 100g to 500mL / 100g; (3) The thickness of the third coating is 50μm to 70μm. In the present application, there are no special restrictions on the sources of the above-mentioned graphite and silicon-oxygen materials, and commercially available products well known to those skilled in the art can be used. Exemplarily, the oil absorption value may be 60mL / 100g, 90mL / 100g, 120mL / 100g, 150mL / 100g, 180mL / 100g, 210mL / 100g, 240mL / 100g, 270mL / 100g, 300mL / 100g, 330mL / 100g, 360mL / 100g, 390mL / 100g, 420mL / 100g, 450mL / 100g, 480mL / 100g, 500mL / 100g, etc.; the thickness of the third coating may be 50μm, 55μm, 60μm, 65μm, 70μm, etc., but is not limited to the listed values, and other unlisted values within this numerical range are also applicable. In the prior art, the silicon-oxygen in the upper layer of the silicon-oxygen system battery is lithiated first due to the high ion concentration. After the silicon-oxygen material is lithiated, the volume expands, which reduces the porosity of the upper layer of the electrode sheet, resulting in insufficient lithium ion channels in the lower layer. In the present application, the third coating uses a silicon-oxygen material with strong fast-charging capability combined with graphite to improve the fast-charging capability of the battery and increase the energy density of the lithium battery. In the present application, the first coating forms a stable bond with the current collector, and the third coating contains silicon-oxygen material and graphite to provide capacity; the second coating forms an ion conduction network by means of the oxide electrolyte therein, which equalizes the concentration distribution of lithium ions in the electrolyte between the coatings and reduces the local ion concentration difference. As a result, the lithiation process of the silicon-oxygen material in the third coating is more uniform, the concentrated expansion caused by excessively high local ion concentration is alleviated, the interfacial stress is reduced accordingly, a good connection is maintained between the active layer and the current collector, the interlayer lithium ion conduction capability is guaranteed, thereby reducing the risk that the surface silicon-oxygen material separates from the current collector due to volume expansion during the lithiation process.

[0035] In one embodiment of the present application, the third conductive agent includes at least one of super conductive carbon black (SP) and acetylene carbon black.

[0036] In one embodiment of the present application, the third coating includes a third active material, a third dispersant, a third binder and a third conductive agent, and the mass ratio of the third active material, the third dispersant, the third binder and the third conductive agent is 90%~97%: 0.5%~5%: 1%~8%: 0.5%~5%.

[0037] In one embodiment of this application, both the first and second conductive agents include carbon nanotubes (CNTs), and the third conductive agent includes superconducting carbon black (SP). The first and second coatings increase the electronic conductivity of the electrode by adding CNTs, which have long-range conductivity. Simultaneously, the third coating uses SP with a high oil absorption value to increase the electrode's liquid retention and conductivity. This allows CNTs and SP to jointly construct the electrode's conductive network in different coatings, exerting a synergistic effect.

[0038] In one embodiment of this application, the graphite:silicon oxide material ratio in the third active material is calculated to be 1 to 99:1 by mass.

[0039] In one embodiment of this application, the first dispersant, the second dispersant, and the third dispersant are each independently selected from at least one of carboxymethyl cellulose, styrene-butadiene rubber, and polyacrylic acid. This application does not impose any special restrictions on the source of the aforementioned first dispersant, second dispersant, and third dispersant; commercially available products well known to those skilled in the art can be used.

[0040] In one embodiment of this application, the first adhesive, the second adhesive, and the third adhesive are each independently selected from at least one of polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic-modified styrene-butadiene rubber, epoxy resin, and nylon. This application does not impose any special restrictions on the source of the aforementioned first adhesive, second adhesive, and third adhesive; commercially available products well known to those skilled in the art can be used.

[0041] According to a second aspect of this application, this application provides a method for preparing the negative electrode sheet as described above, comprising the following steps: S1. The active material is subjected to plasma treatment to obtain a modified active material; S2. The modified active material, a functionalized conductive agent, a binder, and a solvent are mixed to obtain a negative electrode slurry; S3. The negative electrode slurry is coated on the surface of a current collector, and then dried and rolled to obtain a negative electrode sheet.

[0042] The preparation method provided in this application first introduces amino or hydroxyl groups into the active material through plasma treatment. This dry process is solvent-free and does not introduce impurity ions, avoiding the damage to the battery system caused by residual salt ions or acid radicals in liquid-phase methods. Plasma only modifies a few nanometers of the material surface, without destroying the structure of the active material, preventing the over-oxidation, delamination, and decreased conductivity common in liquid-phase oxidation. Furthermore, the plasma treatment speed is as fast as seconds or minutes, applicable to both powders and thin films, with good uniformity, and easy to scale up. Plasma can generate amino groups in one step, eliminating the need for multi-step reactions. During the treatment, the surface of the activated material is simultaneously etched, increasing its roughness, which provides abundant binding sites for subsequent grafting reactions with carboxyl-containing conductive agents. The chemical bonds formed by grafting establish a stable connection between the active material and the conductive agent, making the conductive network less prone to detachment and failure during cycling. By adjusting the plasma power, gas pressure, and treatment time, the type and density of amino groups can be precisely controlled, thereby allowing for flexible adjustment of grafting efficiency and electrode performance.

[0043] In one embodiment of this application, the plasma treatment step includes: performing plasma treatment on the active material under a treatment atmosphere; the treatment atmosphere includes a modified gas and an inert gas, and the modified gas includes at least one of ammonia, hydrazine, O2, air, water vapor, and alcohol vapor.

[0044] In one embodiment of this application, the inert gas includes nitrogen, argon, or helium. This application does not impose any special restrictions on the source of the aforementioned inert gas or modified gas; commercially available products well-known to those skilled in the art can be used.

[0045] In one embodiment of this application, the volume percentage of the modified gas in the processing atmosphere is 40% to 60%. Exemplarily, the volume percentage of the modified gas can be 40%, 42%, 44%, 46%, 48%, 50%, 52%, 54%, 56%, 58%, 60%, etc.; but it is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0046] In one embodiment of this application, the plasma treatment includes pulse treatment, the power of which is 200W to 450W, the pulse treatment includes multiple single pulse treatments, the duration of which is 20 seconds to 30 seconds, the interval between which is 40 seconds to 60 seconds, and the total duration of which is 15 minutes to 25 minutes. For example, the power of pulse processing can be 200W, 250W, 300W, 350W, 400W, etc.; the duration of a single pulse processing can be 20 seconds, 22 seconds, 24 seconds, 26 seconds, 28 seconds, 30 seconds, etc.; the interval between single pulse processing can be 40 seconds, 42 seconds, 44 seconds, 46 seconds, 48 ​​seconds, 50 seconds, 52 seconds, 54 seconds, 56 seconds, 58 seconds, 60 seconds, etc.; the total duration of pulse processing can be 15 minutes, 17 minutes, 19 minutes, 21 minutes, 23 minutes, 25 minutes, etc.; but it is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0047] According to a third aspect of this application, this application provides a battery comprising a negative electrode sheet as described above, or a negative electrode sheet prepared by the above preparation method.

[0048] The technical solution of this application has at least the following beneficial effects: The negative electrode sheet provided by this application forms a chemical bond between the active material and the conductive agent by connecting amino or hydroxyl groups to the surface of the active material and reacting with the carboxyl groups on the surface of the conductive agent. Utilizing this chemical bond, the negative electrode sheet provided by this application can maintain a stable electrode structure even after reducing the binder content; furthermore, it can improve the contact gap, interfacial impedance, and dispersion uniformity between the active material and the conductive agent, thereby increasing the electron transport rate, enhancing the structural stability of the electron channel, and providing microscopic protection for high-rate charge / discharge and cycle stability.

[0049] To further illustrate this application, the following experimental groups are described in detail. Unless otherwise specified, all raw materials used in the following experimental groups of this application are commercially available.

[0050] Example 1 1. Preparation of modified active materials In this embodiment, graphite was used as the raw material to prepare the modified active material. The graphite was then subjected to plasma treatment to obtain the modified active material. Specifically, the plasma treatment was performed using a modifying gas (hydrazine) and an inert gas (argon) as the treatment atmosphere, with the modifying gas accounting for 50% of the volume in the treatment atmosphere. The pulse treatment power was 400W, the duration of a single pulse treatment was 30 seconds, the interval between single pulse treatments was 60 seconds, and the total duration of the pulse treatment was 20 minutes. After the above plasma treatment, amination-modified graphite was obtained.

[0051] 2. Preparation of negative electrode sheet The following are the preparation steps of the negative electrode in this embodiment.

[0052] Preparation of the first coating: The aminated graphite, the first dispersant (sodium carboxymethyl cellulose, CMC-Na), the first binder (styrene-butadiene rubber, SBR), and the first conductive agent (carboxyl-modified CNT) obtained above were weighed in a mass ratio of 93%:1%:1%:5%. These materials were then mixed with water to obtain a first slurry. The first slurry was then coated onto the surface of a copper foil current collector with a thickness of 4.5 μm to obtain the first coating. The areal density of the first coating was 0.0464 mg / mm². 2 The thickness after roll forming is 55μm.

[0053] Preparation of the second coating: The aminated graphite, the second dispersant (CMC-Na), the second binder (SBR), the second conductive agent (carboxyl-modified CNT), and the oxide electrolyte (LLZO, D50 < 500 nm, D90 < 900 nm) obtained above were weighed in a mass ratio of 87%:1%:1%:5%:6%. These materials were then mixed with water to obtain a second slurry. The second slurry was then coated onto a surface away from the current collector and close to the first coating to obtain the second coating. The areal density of the second coating was 0.01688 mg / mm². 2 The thickness after rolling is 20 μm. The carboxyl-modified CNTs were prepared as follows: CNTs were added to a mixed acid (a mixture of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1) to obtain a mixed solution, with a solid-liquid ratio of 0.1–0.2 g CNTs / 50 mL of mixed acid. The mixed solution was ultrasonicated in a water bath for 30–60 minutes, followed by reflux treatment in an oil bath at 60–80 °C for 4–12 hours. After the reaction, the reaction system was cooled to room temperature and diluted with a large amount of ice water while stirring (to prevent bumping). The solution was then filtered through a 0.22 μm PTFE membrane and repeatedly washed with deionized water until the pH of the filtrate was approximately 7. Finally, the solution was vacuum dried at 60 °C for 12–24 hours to obtain the carboxyl-modified CNTs.

[0054] Preparation of the third coating: Graphite, silicon oxide, third dispersant (CMC-Na), third binder (polyacrylic acid, PAA), and third conductive agent (SP) were weighed in a mass ratio of 76.4%:18.6%:1%:2%:2%. These materials were then mixed with water to obtain a third slurry. This third slurry was then coated onto the surface of the first coating adjacent to the second coating to obtain the third coating. The areal density of the third coating was 0.0464 mg / mm². 2 The thickness after roll forming is 55μm.

[0055] Example 2 This embodiment prepares the negative electrode sheet according to the formula and method provided in Example 1. The difference from Example 1 is that in this embodiment, during the preparation of the negative electrode sheet, the second slurry is mixed with an aminated graphite: second dispersant (CMC-Na): second binder (SBR): second conductive agent (carboxyl-modified CNT): oxide electrolyte (NASICON and LATP, D50 < 500nm, D90 < 900nm) in a mass ratio of 88%:0.3%:1.7%:5%:5%; and the third slurry is mixed with graphite:siloxane: third dispersant (CMC-Na), third binder (PAA): third conductive agent (SP) in a mass ratio of 75.81%:19.19%:1%:2%:2%. Apart from the above differences, the operation steps and other parameter controls for preparing the negative electrode sheet in this embodiment are strictly consistent with those in Example 1.

[0056] Example 3 This embodiment prepares the negative electrode sheet according to the formula and method provided in Example 2. The difference from Example 2 is that in this embodiment, when preparing the negative electrode sheet, the first coating (with an areal density of 0.0514 mg / mm²) is... 2 The thickness of the roll-pressed coating is 60 μm, and the second coating (area density is 0.006752 mg / mm²) has a thickness of 60 μm. 2 The thickness of the roll-pressed coating is 10 μm, and the third coating (area density is 0.051485 mg / mm²) 2 The thickness of the negative electrode after rolling is 60 μm. Apart from the differences mentioned above, the operation steps and other parameter controls for preparing the negative electrode in this embodiment are strictly consistent with those in Example 2.

[0057] Example 4 This embodiment prepares the negative electrode sheet according to the formula and method provided in Example 1. The difference from Example 1 is that in this embodiment, during the preparation of the negative electrode sheet, the third slurry is mixed with graphite in a mass ratio of 86.4% : 8.6% : 1% : 2% : 2% for the third dispersant (CMC-Na) and the third binder (PAA) : the third conductive agent (SP). Apart from the above differences, the operation steps and other parameter controls for preparing the negative electrode sheet in this embodiment are strictly consistent with those in Example 1.

[0058] Example 5 This embodiment prepares the negative electrode sheet according to the formula and method provided in Example 4. The difference from Example 4 is that ammonia is used as the modifying gas in the preparation of the modified active material in this embodiment. Apart from the above differences, the operation steps and other parameter controls for preparing the negative electrode sheet in this embodiment are strictly consistent with those in Example 4.

[0059] Example 6 This embodiment prepares the negative electrode sheet according to the formula and method provided in Example 1. The difference from Example 1 is that the thickness of the second coating after rolling is 30 μm when preparing the negative electrode sheet in this embodiment. Apart from the above differences, the operation steps and other parameter control for preparing the negative electrode sheet in this embodiment are strictly consistent with those in Example 1.

[0060] Example 7 This embodiment prepares the negative electrode sheet according to the formula and method provided in Example 1. The difference from Example 1 is that no second coating is applied when preparing the negative electrode sheet in this embodiment. Apart from the above differences, the operation steps and other parameter controls for preparing the negative electrode sheet in this embodiment are strictly consistent with those in Example 1.

[0061] Example 8 This embodiment prepares the negative electrode sheet according to the formula and method provided in Example 1. The difference from Example 1 is that in this embodiment, graphite is used in an equal mass fraction to replace silicon oxide material in the third slurry during the preparation of the negative electrode sheet. Apart from the above differences, the operation steps and other parameter controls for preparing the negative electrode sheet in this embodiment are strictly consistent with those in Example 1.

[0062] Comparative Example 1 This comparative example prepares a negative electrode sheet according to the formulation and method provided in Example 1. The difference between this comparative example and Example 1 is that conventional CNTs without carboxyl modification and conventional graphite without amylation modification are used in both the first and second coatings. Apart from the above differences, the operation steps and other parameter control of this comparative example are strictly consistent with those of Example 1.

[0063] Comparative Example 2 This comparative example prepares a negative electrode sheet according to the formulation and method provided in Example 1. The difference between this comparative example and Example 1 is that, in the preparation of the negative electrode sheet, equal parts by mass of SP are used to replace carboxyl-modified CNTs in the first coating and the second coating, respectively. Apart from the above differences, the operation steps and other parameter control of the negative electrode sheet preparation in this comparative example are strictly consistent with those in Example 1.

[0064] Comparative Example 3 This comparative example prepares a negative electrode sheet using the formulation and method provided in Example 1. The difference between this comparative example and Example 1 is that, in preparing the negative electrode sheet, the aminated graphite prepared in Example 1 is replaced with an equal mass fraction of graphite in the first coating and the second coating, respectively. Apart from the above differences, the operation steps and other parameter controls for preparing the negative electrode sheet in this comparative example are strictly consistent with those in Example 1.

[0065] Comparative Example 4 This comparative example prepares the negative electrode sheet using the formula and method provided in Comparative Example 1. The difference is that, in this comparative example, the mass content of the binder in the first and second coatings is increased to 5.5% (achieved by reducing the mass content of graphite). Apart from the above differences, the operating steps and other parameter controls for preparing the negative electrode sheet in this comparative example are strictly consistent with those in Comparative Example 1.

[0066] Comparative Example 5 The negative electrode sheet provided in this comparative example has a single-layer structure. Specifically, unmodified graphite, dispersant (CMC-Na), binder (SBR), and unmodified CNTs were weighed in a mass ratio of 95%:1%:2%:2%, and then mixed with water to obtain a slurry. This slurry was then coated onto the surface of a copper foil current collector with a thickness of 4.5 μm to obtain a coating. The areal density of the coating is 0.109722 mg / mm². 2 The thickness after roll forming is 130μm.

[0067] Comparative Example 6 The negative electrode sheet provided in this comparative example has a single-layer structure. Specifically, unmodified graphite, dispersant (CMC-Na), binder (SBR), and SP are weighed in a mass ratio of 95%:1%:2%:2%, and then mixed with water to obtain a slurry. This slurry is then coated onto the surface of a copper foil current collector with a thickness of 4.5 μm to obtain a coating. The areal density of the coating is 0.109722 mg / mm². 2 The thickness after roll forming is 130μm.

[0068] Test case 1. Test Object Using the negative electrode sheets prepared in each embodiment and comparative example as test samples, and lithium metal as the counter electrode, coin cell test half-cells were assembled. The assembly sequence was as follows: negative electrode shell, spring sheet, gasket, lithium metal, separator, negative electrode sheet (circular diameter 12mm), gasket, positive electrode shell, after which 60μL of electrolyte was injected, and then pressed into a coin cell. The separator was a 7-micron thick PE separator, and the electrolyte weight ratio was LiPF6: EC: EMC: DEC = 15%: 28.3%: 28.4%: 28.3%.

[0069] 2. Testing Methods (1) Capacity retention rate at 0.3C, 0.5C, and 1C: The battery under test was placed in an environment of 25°C and left to stand for 6 hours. Then, it was discharged at a constant current of 0.1C until the voltage dropped to 0.005V, left to stand for 30 minutes, and then discharged at a constant current of 0.05C until 0.005V, left to stand for 30 minutes. Next, it was charged at a constant current of 0.3C to 2V, left to stand for 30 minutes, and the charging capacity at this rate was recorded as the 0.3C capacity retention rate. Then, the above discharge (0.1C + 0.05C) and standing steps were repeated, and then it was charged at a constant current of 0.5C to 2V, left to stand for 30 minutes, and the charging capacity was recorded as the 0.5C capacity retention rate. The same discharge and standing steps were repeated again, and finally, it was charged at a constant current of 1C to 2V, left to stand for 30 minutes, and the charging capacity was recorded as the 1C capacity retention rate.

[0070] (2) Number of cycles to reach 80% SOH at 0.5C: Charge at 0.5C constant current to 2V, let stand for 30 minutes, then discharge at 0.5C constant current to 0.005V, let stand for 30 minutes. This process is counted as one cycle. Repeat this charge-discharge cycle and record the discharge capacity of each cycle in real time. When the discharge capacity decays to 80% of the discharge capacity of the first cycle (i.e., SOH drops to 80%), the accumulated number of cycles is the cycle life of the battery under 0.5C conditions. The entire cycle test is also performed in a constant temperature environment of 25℃, and all charge and discharge are in constant current mode (CC), with the cutoff conditions being the same as described above.

[0071] 3. Test Results and Analysis The test results of this test example are shown in Table 1. Comparison of the data from Examples 1-8 and Comparative Examples 1-6 shows that the negative electrode sheet provided by this invention exhibits good capacity retention under test conditions of 0.3C, 0.5C, and 1C. In particular, comparison of Example 1, Comparative Example 1, and Comparative Example 4 demonstrates that this invention utilizes the synergistic effect of modified CNTs (containing carboxyl groups) and modified active materials (containing amino groups) to reduce the amount of binder, thereby improving the fast-charging performance of the negative electrode sheet while also extending its service life.

[0072] Furthermore, the thickness of the second coating is preferably less than that of the first and third coatings. This is because the second coating serves as an ion channel for the first and third coatings, and its higher oxide electrolyte content reduces the ion concentration difference between the two coatings. However, according to data from Examples 1 and 6, when the thickness of the second coating is too large, it increases the ion migration path and reduces the proportion of active material in the overall negative electrode, thus affecting the fast-charging performance of the negative electrode. According to data from Examples 1 and 7, when the second coating is not provided, the loss of ion transport channels leads to significant differences in the lithium ion concentration of the electrolyte in each coating, resulting in a decrease in cycle performance and capacity retention at each rate.

[0073] Furthermore, based on the data from Examples 1, 8, 2, and 3, it can be seen that although silicon-oxygen materials theoretically support faster charging speeds, the introduction of silicon-oxygen leads to rapid volume expansion that compresses the pores of the upper layer of the electrode when lithium is preferentially intercalated due to its higher ion concentration. This obstructs the lithium-ion transport channels in the lower layer, thus hindering the overall fast-charging performance. In contrast, this invention alleviates the stress caused by silicon volume expansion through a three-layer structure design and stabilizes the electronic pathways using the chemical bonds between the modified active material and the functionalized conductive agent. This allows the high capacity advantage of silicon-oxygen to be fully utilized while mitigating its impact on fast-charging performance.

[0074] Furthermore, the negative electrode sheet provided in Application Example 1 has a coin cell capacity of 4.973 mAh and an active material mass of 11.78 mg; the negative electrode sheet provided in Comparative Example 5 has a coin cell capacity of 4.124 mAh and an active material mass of 11.72 mg. This demonstrates that compared to negative electrode sheets prepared by single-layer coating, the negative electrode sheet provided by this invention, through its structural design and the incorporation of specific modified active materials and functionalized conductive agents, can significantly improve its capacity, indicating that improving the electron-ion network can effectively enhance battery capacity. Moreover, combining Comparative Examples 1 and 4, it can be seen that in the prior art, insufficient binder leads to rapid capacity decay; while when the binder content in the active coating is greater than 5%, although it can improve lifespan, it results in higher internal resistance, thus affecting fast-charging performance.

[0075] Table 1. Test results of this test case

[0076] The above embodiments are only used to illustrate the technical solutions of this application and are not intended to limit the scope of protection of this application. Although this application has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of this application without departing from the substance and scope of the technical solutions of this application.

Claims

1. A negative electrode sheet, characterized in that, The negative electrode includes a current collector; An active coating, comprising modified active materials, functionalized conductive agents, and binders. In the active coating, the adhesive has a mass percentage of ≤5%; The modified active material contains amino or hydroxyl groups, and the functionalized conductive agent contains carboxyl groups.

2. The negative electrode sheet as described in claim 1, characterized in that, The negative electrode includes: A first coating is disposed on the surface of the current collector; A second coating is disposed on the surface of the first coating away from the current collector; The first coating comprises a first active material, a first conductive agent, and a first binder; the second coating comprises a second active material, a second conductive agent, and a second binder. The first active material, and / or the second active material includes the modified active material; The first conductive agent, and / or the second conductive agent includes the functionalized conductive agent.

3. The negative electrode sheet as described in claim 2, characterized in that, At least one of the following conditions must be met: (1) The first active material and / or the second active material includes at least one of graphite, hard carbon, and lithium titanate; (2) In the first active coating, the mass percentage of the first adhesive is 0.5% to 4%, and / or, in the second active coating, the mass percentage of the second adhesive is 0.5% to 4%; (3) Both the first active material and the second active material include the modified active material; (4) Both the first conductive agent and the second conductive agent include the functionalized conductive agent; (5) The first conductive agent and / or the second conductive agent includes carbon nanotubes, wherein the length of the carbon nanotubes is 5 μm to 30 μm and the diameter of the carbon nanotubes is 0.4 nm to 2 nm; (6) The thickness of the first coating is 50μm~70μm, and the thickness of the second coating is 5μm~20μm.

4. The negative electrode sheet as described in claim 2, characterized in that: The second coating also includes an oxide electrolyte, which includes at least one of lithium lanthanum zirconium oxide electrolyte material, sodium superionic conductor electrolyte material, and lithium titanium aluminum phosphate electrolyte material.

5. The negative electrode sheet as described in claim 2, characterized in that, The negative electrode also includes: A third coating is disposed on the surface of the second coating away from the current collector; The third coating includes a third active material, which includes a silicon-based material.

6. The negative electrode sheet as described in claim 5, characterized in that, At least one of the following conditions must be met: (1) The third active material includes graphite and silicon-oxygen materials, wherein the chemical formula of the silicon-oxygen materials is SiO2. x , of which 0 <x≤2; (2) The third coating also includes a third conductive agent, wherein the oil absorption value of the third conductive agent is 60mL / 100g~500mL / 100g; (3) The thickness of the third coating is 50μm~70μm.

7. The negative electrode sheet as described in claim 6, characterized in that: In the third active material, the ratio of graphite to silicon oxide is calculated to be 1 to 99:1 by mass.

8. A method for preparing a negative electrode sheet as described in any one of claims 1 to 7, characterized in that, Includes the following steps: S1. The active material is subjected to plasma treatment to obtain the modified active material; S2. The modified active material, the functionalized conductive agent, the binder, and the solvent are mixed to obtain a negative electrode slurry; S3. The negative electrode slurry is coated on the surface of the current collector, and then dried and rolled to obtain the negative electrode sheet.

9. The preparation method according to claim 8, characterized in that, The plasma treatment step includes: performing plasma treatment on the active material under a treatment atmosphere; the treatment atmosphere includes a modified gas and an inert gas, and the modified gas includes at least one of ammonia, hydrazine, O2, air, water vapor, and alcohol vapor.

10. A battery, characterized in that, The battery includes a negative electrode sheet as described in any one of claims 1 to 7, or a negative electrode sheet prepared by any one of claims 8 to 9.